SOVEREIGNTY, DIPLOMACY AND DEMOCRACY: THE CHANGING CHARACTER OF “INTERNATIONAL REPRESENTATION” — FROM STATE TO SELF - Alan K. Henrikson (Сравнительная политика)
Addressing (the question of) a new diplomacy for the 21st century, Alan Henrikson reflects philosophically and historically upon a shift that may be occurring from the sovereign State, with ambassadors serving as formal representatives of entire nations, to the autonomous Self, with individual persons, employing social media, being able to represent themselves, and their group concerns, to the world. Will the Leviathan of Thomas Hobbes be replaced by the Facebook social graph as the pattern for the next world order? The traditional institutions of diplomacy—and professional diplomats—are being challenged, are now adapting, and are still vital to the making and carrying out of the international agreements needed if global issues are to be resolved.